2019
DOI: 10.1136/bcr-2018-226518
|View full text |Cite
|
Sign up to set email alerts
|

Hunter syndrome with persistent thrombocytopenia

Abstract: A case of Hunter syndrome, 6½-year-old boy presented with persistent thrombocytopenia and bleeding diathesis. However, cytopenia is not a usual presentation in patients with mucopolysaccharidosis II. After ruling out other causes of severe thrombocytopenia, a clinical possibility of chronic Epstein-Barr virus (EBV) infection was considered. He was treated with intravenous immunoglobulin for refractory thrombocytopenia and intracranial bleed. This was followed by oral prednisolone. The EBV serology was found po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Earlier, a family with 2 affected sibling with Hunter syndrome has been described from our centre, the older child had persistent thrombocytopenia. [5] In present series, 41% MPS patients presented with recurrent respiratory problems. Thus, in children with recurrent respiratory problems, a high index of suspicion should be kept for MPS, and a skeletal survey should be performed.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Earlier, a family with 2 affected sibling with Hunter syndrome has been described from our centre, the older child had persistent thrombocytopenia. [5] In present series, 41% MPS patients presented with recurrent respiratory problems. Thus, in children with recurrent respiratory problems, a high index of suspicion should be kept for MPS, and a skeletal survey should be performed.…”
Section: Discussionmentioning
confidence: 46%
“…Immune thrombocytopenia was due to Epstein Barr viral infection which further complicated the presentation. [5] Skin manifestations were present in 57% of the cases in form of Mongolion spots, callosities over joints. Seizures and behavioural abnormalities were also present in significant proportion; one child had attention deficit hyperactivity disorder (ADHD) requiring treatment with risperidone.…”
Section: Resultsmentioning
confidence: 99%
“…As heparan sulfate is known to have structural and functional similarity to heparin [15][16][17], a well-known entity, called HIT, should be considered. Most research [1,6,7,9,10] reported the efficacy of immunomodulatory/immunosuppressive therapy (intravenous immunoglobulin and corticosteroids) for thrombocytopenia in MPS II and III patients and encountered in one of our patients, is in accordance with HIT. Furthermore, cases of spontaneous HIT after orthopedic surgery have been described and judged to be the result of glycosaminoglycans' release, triggering the generation of complexes with PF4 and subsequent antibody production [18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 61%
“…Nevertheless, less increasing number of case reports describing thrombocytopenia in patients with Hunter and Sanfilippo syndromes [1][2][3][4][5][6][7][8][9] and even in a child with unspecified type of MPS [10] have appeared in recent years. Some of the articles described clinical manifestations of thrombocytopenia, including serious complications: intracranial hemorrhage, recurrent epistaxis, melena and anemia, extradural hemorrhage following ventriculoperitoneal shunt insertion, intraoperative bleeding during adenoidectomy, epistaxis, and skin hemorrhages [1,3,6,7,8,10]. Notably, most cases of low platelet count were encountered in patients with heparan sulfate breakdown failure (namely MPS II and III).…”
Section: Introductionmentioning
confidence: 99%
“…In MPS II idiopathic thrombocytopenic purpura (ITP) was documented ( 245 , 246 ). In two other MPS II siblings it was accompanied by pancytopenia after ERT ( 247 ).…”
Section: Hematologymentioning
confidence: 99%